TAJOG RUN GAME VISUAL ASSET DESIGN - Yasa, I Wayan Adi Putra; Yasa, Ngakan Putu Dharma (Yayasan Sinergi Widya Nusantara, 2024)
Purpose : designing character design assets, item, obstacles and background for the development of the Tajog Run game. Research methods : research start from determining the visual style based on the game concept, media and user segmentation. After that, visual study process are collected into a moodboard. After that, brainstorming is carried out to get appropriate visuals in the form of design sketches, then enter the visualization stage using a computer/laptop device. Findings : through the process of visual study, brainstorming, and visualization, suitable design assets were obtained in the form of boy character assets in typical Balinese clothing, item assets in the form of stars, chicken and stone obstacle assets, background assets with a forest environment full of trees. Implications: obtain game visual assets that are suitable for the children's market segmentation